OP40 Selenium Supplementation for the Primary Prevention of Cardiovascular Disease (CVD) – A Cochrane Systematic Review. (17th September 2012) - Rees, K; Hartley, L; Day, C; Clarke, A; Stranges, S
Abstract : Background: Selenium is a key component of a number of selenoproteins which protect against oxidative stress and have the potential to prevent chronic diseases including CVD. However, observational studies have shown inconsistent associations between selenium intake and CVD risk; in addition there is concern around an increased risk of type 2 diabetes with high selenium exposure. Objective: To determine the effectiveness of selenium only supplementation for the primary prevention of CVD and examine potential adverse effects on type 2 diabetes. Methods: The following electronic databases were searched with no language restrictions from their inception to July 2011: MEDLINE, EMBASE, CINAHL, Web of Science, the Cochrane Library and trial registers. Studies were included if they fulfilled the following criteria: study design - RCTs, participants - free of CVD (includes those at high risk), intervention - selenium only supplementation, comparator – no intervention or placebo, outcomes – diagnosis of CVD or change in the risk factor profile for CVD (blood pressure, lipids) or adverse effects (type 2 diabetes). Two reviewers independently screened titles and abstracts, assessed shortlisted studies for formal inclusion/exclusion, abstracted data and assessed methodological quality. Data were analysed using RevMan 5.1 software. Results: Database searching resulted in 1310 hits of which 43 went forward for formal inclusion/exclusion; 9 RCTs met the inclusion criteria. Included trials were heterogeneous in the participants recruited, dose of selenium, intervention and follow-up periods, outcomes reported, country of recruitment and baseline selenium status. Meta-analysis was possible for 2 trials reporting clinical events, but the analysis was dominated by the SELECT trial which carried over 80% of the weight. There were no statistically significant effects of selenium supplementation on total mortality (RR 0.97, 95% CI 0.88, 1.08), CVD mortality (RR 0.97, 95% CI 0.79, 1.2) or non-fatal CVD events (RR 0.97, 95% CI 0.9, 1.05). Similarly, the SELECT trial dominated the findings from 3 trials reporting type 2 diabetes, where selenium supplementation increased the risk of type 2 diabetes (RR 1.06, 95%CI 0.97, 1.16) although this did not reach statistical significance. There were no statistically significant effects of selenium on total or HDL cholesterol (measured in 2 trials (5 intervention arms) with varying doses of selenium supplementation). Conclusion: There is still a lack of evidence of the effects of selenium supplementation in the primary prevention of CVD. More trial evidence is needed especially to clarify the potential adverse effect of selenium supplementation on type 2 diabetes.